2021
DOI: 10.1002/cphc.202100132
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and Theoretical Evidences of Anion⋅⋅⋅Anion Interaction

Abstract: Planar (HgCl3)− anions are stacked fairly closely together in a slipped parallel arrangement within several crystal structures. Quantum chemical analysis shows evidence of strong noncovalent spodium bonds between the Hg π‐hole of one unit and the Cl atom of an adjacent unit. Anion⋅⋅⋅anion spodium bonds work in tandem with crystal packing forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…and below the Au atom (p-holes, the terms s/p-hole are used also for regions with negative potential [20,23,30] ). The MEP values are similar at both types of holes (À79.6 and À78.3 kcal mol À1 for s and p-holes, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and below the Au atom (p-holes, the terms s/p-hole are used also for regions with negative potential [20,23,30] ). The MEP values are similar at both types of holes (À79.6 and À78.3 kcal mol À1 for s and p-holes, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Computations show that these interactions are attractive, and their orthogonal directionality is consistent with p-hole CiBs. [15] Anion•••anion interactions enabled by hydrogen bonds, [44] halogen bonds, [45] or involving perhalometallate anions of Groups 2, [46] 3, [24] and 12 [20,23] elements have been rationalized by anisotropic distribution of the electron density in the anions. Interestingly, the same theoretical approach was used to analyze the effects overcoming anion-anion Coulomb repulsions and allowing the formation of stable adducts PnCl 4 À •••CN À (Pn = P, As, Sb), wherein the PnCl 4 À anion adopts a square-planar geometry similar to that of AuCl 4 À .…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Computations show that these interactions are attractive, and their orthogonal directionality is consistent with π‐hole CiBs [15] . Anion ⋅⋅⋅ anion interactions enabled by hydrogen bonds, [44] halogen bonds, [45] or involving perhalometallate anions of Groups 2, [46] 3, [24] and 12 [20, 23] elements have been rationalized by anisotropic distribution of the electron density in the anions. Interestingly, the same theoretical approach was used to analyze the effects overcoming anion–anion Coulomb repulsions and allowing the formation of stable adducts PnCl 4 − ⋅⋅⋅ CN − (Pn=P, As, Sb), wherein the PnCl 4 − anion adopts a square‐planar geometry similar to that of AuCl 4 − [47] .…”
Section: Figurementioning
confidence: 96%
“…[22][23][24][25] Since last year, the related experimental and theoretical studies have been reported for spodium bonds rapidly. [26][27][28][29][30][31][32][33] For the planar structures such as MCl 3 À (M=Zn, Cd, Hg), a π-hole lies directly above each M atom, [26] while a σ-hole is found for it in the nonplanar molecules. [21] The spodium bond is usually present between different or same molecules [27] although intramolecular spodium bond is also described.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] For the planar structures such as MCl 3 À (M=Zn, Cd, Hg), a π-hole lies directly above each M atom, [26] while a σ-hole is found for it in the nonplanar molecules. [21] The spodium bond is usually present between different or same molecules [27] although intramolecular spodium bond is also described. [28,29] Other than molecules with lone pairs, carbenes are also evidenced to be used as the electron donors in the spodium bonds.…”
Section: Introductionmentioning
confidence: 99%